Analisis Efektivitas Biaya Terapi Kombinasi Mood Stabilizer dan Antipsikotik pada Pasien Gangguan Afektif Bipolar di Rawat Inap RSJ Grhasia Yogyakarta - Novi Milasari; Dyah Aryani Perwitasari; Sawitri Sawitri (Jurnal Surya Medika (JSM), 2021)
Bipolar affective disorder is an episodic mental disorder characterized by manic, hypomanic, depressive, and mixed episodes, usually recurring and can last a lifetime. Patients with bipolar disorder have annual medical costs that were four times those of patients without bipolar disorder. The aim of this study is to analyze the cost-effectiveness of combination therapy between mood stabilizers and antipsychotics in patients with the bipolar affective disorder at Grhasia Mental Hospital Yogyakarta. This study is a retrospective with cohort study design using medical records and direct medical cost data during Januari-December 2018 period. Subjects are patients who were diagnosed with bipolar affective disorder manic episode (F31.2) and received a combination of mood stabilizer and antipsychotic therapy. The results were obtained in 46 patients with the affective disorder who met the inclusion criteria. The average direct medical cost of the sodium divalproate group was IDR 6.319.933 per day and in the lithium group was IDR 5.705.953 per day. The average length of stay in the sodium divalproate group was 25,79 days and in the lithium group was 25,75 days (P = 0,991). The Average Cost Effectivity Ratio (ACER) sodium divalproat group is lower than the lithium group (IDR 221.246 per day and IDR 245.434 per day, respectively). The conclusion of this study is that the combination of sodium divalproate-antipsychotic therapy is more cost-effective than lithium-antipsychotic therapy in a patient with bipolar affective disorder manic episode